Influence of Cutting Tool Wear on Contact Stresses and Temperature Distribution in Titanium Alloy Machining; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Kozlov V. N. Victor Nikolayevich; Jia Yu Zhang; Letshiner E. G. Ekaterina Georgievna; Wen Ze Zhao (2017, 2017)
Title screen